(untitled) (Asian Journal of Pharmaceutics (AJP), 2026)
Objective: The objective of the study was to design and evaluate phytopharmaceutical Formulation of flavonoid isolated from Saraca asoca bark for antidepressant activity. Materials and Methods: A silica gel column (60–120 mesh) chromatography method was used to separate the phytoconstituent from the ethanolic extract of S. asoca bark. Direct compression was used to manufacture the mouth-dissolving tablets, which were subsequently assessed for antidepressant activity and other tablet evaluation tests in rats (Institutional Animal Ethics Committee reference number Pharma/FMHS/SGTU/1182), dated 20 September 2021. Results: The produced tablets were mechanically sound, as evidenced by their hardness values of 2.95 ± 0.43 kg/cm2 to 3.85 ± 0.34 kg/cm2 and friability levels of 0.32–0.54%. Weight variation test results were also within tolerance limits, ranging from 3.01% to 4.54% of the mean weight of 10 pills. The tablets were also found to be consistently within the recommended range of 95–105%, with a drug content uniformity test score of 97.83 ± 1.23% to 100.85 ± 1.22%. Disintegration time, 19 s to 55 s, and dispersion time, 60 s to 115 s, were also fine. The optimized formulation demonstrated antidepressant activity, as evidenced by a significant (P < 0.05) reduction in immobility time in both tail suspension test and forced swim test, as well as a significant (P < 0.05) reduction in brain tissue glutamate and nitrite levels in mice treated with the formulation compared to the negative control, as did by the standard drug fluoxetine. Conclusion: Dispersion time has been used to find out the best the formulation. The prepared best formulation, having a minimum dispersion time of 60 s, that is, F12, was observed to obey with entire physical parameters as well as antidepressant action.